Phenoxy Derivatives of Bis (Pyridine) Tungsten(VI) Disulphidodichloride - Dabas, P.; Rastogi, M.K. (Asian Journal of Chemistry, 2010)
A number of phenoxy derivatives of tungsten(VI) disulphidodichloride in pyridine solution have been synthesized. Their physical characteristics, magnetic susceptibility, electronic and IR spectra are reported.